Multiplexed cellular profiling identifies an organoselenium compound as an inhibitor of CRM1‐mediated nuclear export - Jimenez, Lucia (2022)
Chromosomal region maintenance 1 (CRM1 also known as Xpo1 and exportin-1) is the receptor for the nuclear export controlling the intracellular localization and function of many cellular and viral proteins that play a crucial role in viral infections and cancer. The inhibition of CRM1 has emerged as a promising therapeutic approach to interfere with the lifecycle of many viruses, for the treatment of cancer, and to overcome therapy resistance. Recently, selinexor has been approved as the first CRM1 inhibitor for the treatment of multiple myeloma, providing proof of concept for this therapeutic option with a new mode of action. However, selinexor is associated with dose-limiting toxicity and hence, the discovery of alternative small molecule leads that could be developed as less toxic anticancer and antiviral therapeutics will have a significant impact in the clinic. Here, we report a CRM1 inhibitor discovery platform. The development of this platform includes reporter cell lines that monitor CRM1 activity by using red fluorescent protein or green fluorescent protein-labeled HIV-1 Rev protein with a strong heterologous nuclear export signal. Simultaneously, the intracellular localization of other proteins, to be interrogated for their capacity to undergo CRM1-mediated export, can be followed by co-culturing stable cell lines expressing fluorescent fusion proteins. We used this platform to interrogate the mode of nuclear export of several proteins, including PDK1, p110 alpha, STAT5A, FOXO1, 3, 4 and TRIB2, and to screen a compound collection. We show that while p110 alpha partially relies on CRM1-dependent nuclear export, TRIB2 is exported from the nucleus in a CRM1-independent manner. Compound screening revealed the striking activity of an organoselenium compound on the CRM1 nuclear export receptor.